Single-photon-compatible telecommunications-band quantum memory in a hot atomic gas - Thomas,SE; Sagona-Stophel,S; Schofield,Z; Walmsley,IA; Ledingham,PM (Physical Review Applied, 2023)
The efficient storage and on-demand retrieval of quantum optical states that are compatible with the telecommunications band is a requirement for future terrestrial-based quantum optical networking. Spectrum in the telecommunications band minimizes optical fiber-propagation losses, and broad optical bandwidth facilitates high-speed networking protocols. Here we report on a telecommunications-wavelength- and bandwidth-compatible quantum memory. Using the Off-Resonant Cascaded Absorption protocol in hot 87Rb vapor, we demonstrate a total internal memory efficiency of 20.90(1)% with a Doppler-limited storage time of 1.10(2) ns. We characterize the memory performance with weak coherent states and measure a signal-to-noise ratio of 1.9(1)×104 for an average input photon number of 0.084.